2017
DOI: 10.1111/vox.12532
|View full text |Cite
|
Sign up to set email alerts
|

Vox Sanguinis International Forum on platelet cryopreservation

Abstract: Question 4Cryopreserved platelets are currently stored at -65 to -90°C (-80°C) in a mechanical freezer. A frozen shelf life of 2 years has been applied for platelets for the CLIP trial and for the Australian Defence Force. We have allocated a post-thaw shelf life of 6 h for platelets for the Australian Defence Force to minimize risk of bacterial growth. This is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
29
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 25 publications
0
29
0
1
Order By: Relevance
“…Platelet cryopreservation is an attractive alternative to RT storage, and international interest in this storage option has grown considerably in the past decade . For cryopreservation, 5% to 6% dimethyl sulfoxide (DMSO) is added to the platelets and they are frozen and stored at −80°C, which extends their shelf life to at least 2 years .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Platelet cryopreservation is an attractive alternative to RT storage, and international interest in this storage option has grown considerably in the past decade . For cryopreservation, 5% to 6% dimethyl sulfoxide (DMSO) is added to the platelets and they are frozen and stored at −80°C, which extends their shelf life to at least 2 years .…”
mentioning
confidence: 99%
“…Freezing platelets within 2 days of collection reduces the available inventory of liquid‐stored platelets and, combined with unpredictable supply and demand, may actually result in the inability to meet demand for this component. As the clinical indications for liquid‐stored and cryopreserved platelets (CPPs) are likely to be distinct, a flexible approach to the management of these inventories would be beneficial. Potentially, if platelets could be cryopreserved later in their usable shelf life, following storage at RT, this would maximize utility, as they could be available for standard transfusion and then frozen if not required.…”
mentioning
confidence: 99%
“…To date, CPPs have been deployed in a number of military missions and confirmed to be effective in treating bleeding casualties, but have not been authorized for use in civilians in any country, with the main concern being the safety of CPPs for transfusion. Controlled clinical trials to demonstrate safety and efficacy are under way in several countries, but definitive results have not yet been obtained . Over the past 40 years, the cellular mechanisms of coagulation and thrombin generation have been widely investigated and are helpful for understanding the efficacy of CPPs, but reports on the mechanism of adverse reactions to CPP transfusion are scarce.…”
mentioning
confidence: 99%
“…These studies have been extensively reviewed . A modification of this technique for which thawed PLTs were resuspended in plasma rather than saline was used by the Dutch military in Bosnia and Afghanistan and adopted by other groups …”
Section: Cryopreserved Pltsmentioning
confidence: 99%
“…39 A modification of this technique for which thawed PLTs were resuspended in plasma rather than saline was used by the Dutch military in Bosnia and Afghanistan and adopted by other groups. 40,41 In vitro and ex vivo studies of cryopreserved PLTs have shown promising results. In a baboon model, 54% of thawed cryopreserved PLTs were recovered 2 hours after transfusion, more than that for liquid PLTs stored for 5 days.…”
Section: Cryopreserved Pltsmentioning
confidence: 99%